In vitro activity of gepotidacin against urine isolates of Escherichia coli from outpatient departments in Germany. (7th December 2022) - Kresken, Michael; Wohlfarth, Esther; Weikel, Chase; Butler, Deborah; Pfeifer, Yvonne; Werner, Guido; ,
Abstract: Background: Escherichia coli is the leading pathogen of community-acquired urinary tract infections. Gepotidacin is a novel, bactericidal, first-in-class triazaacenaphthylene oral antibiotic that inhibits bacterial DNA replication by a distinct mechanism of action that confers activity against most strains of target pathogens, such as E. coli, Staphylococcus saprophyticus and Neisseria gonorrhoeae, including those resistant to other antibiotics. Objectives: This study assessed the in vitro activity of gepotidacin in comparison with ciprofloxacin and other oral standard-of-care antibiotics using a large collection of urine isolates of E. coli obtained from outpatients in Germany. Methods: Four hundred and sixty E. coli collected from 23 laboratories during a surveillance study in 2019/2020 were tested. Forty-six isolates (10.0%) produced an ESBL of the CTX-M family, half of which belonged to MDR clonal subgroups of E. coli ST131. Antibiotic susceptibilities were tested at a reference laboratory by broth microdilution according to the standard ISO 20776-1. Results: Fifty-three (11.5%) isolates were ciprofloxacin resistant, 25 (47.2%) of which also produced an ESBL. Overall, MIC50/90 values for gepotidacin were 2/4 mg/L (MIC range 0.125–16 mg/L), with no differences in activity between ciprofloxacin-susceptible and ciprofloxacin-resistant isolates, ESBL-producing and non-ESBL isolates, O25b-ST131 isolates, and isolates susceptible or resistant to fosfomycin, mecillinam or nitrofurantoin. Conclusions: Gepotidacin showed promising in vitro activity against urine isolates of E. coli, including ciprofloxacin-resistant isolates, ESBL-producing isolates and isolates resistant to oral standard-of-care antibiotics.